Equilibrium unemployment under negotiated profit sharing - Erkki Koskela; Rune Stenbacka (Bank of Finland, 2003)
We study employment, employee effort, wages and profit sharing when firms face stochastic revenue shocks and when base wages and profit shares are determined through collective bargaining.The negotiated profit share depends positively on the relative bargaining power of the trade union and has effort-enhancing and wage-moderating effects.We show that higher profit sharing reduces equilibrium unemployment under circumstances with sufficiently rigid labour market institutions, ie sufficiently high benefit- replacement ratios and relative bargaining powers of trade unions.Conversely, profit sharing seems to be destructive from the point of view of employment when the labour market rigidities are sufficiently small.
URN:NBN:fi:bof-20140807266
Keywords: J51; J41; G32; 330; wage bargaining; profit sharing; efficiency wages; equilibrium unemployment